The effect of body shaming on students who blame themselves - Hariyati, Rita; Setiawan, Muhammad Andri; Sulistiyana, Sulistiyana (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
Teenagers often become victims and perpetrators of body shaming carried out by those closest to them, such as family, community, and friends, by joking. Ignorant adolescents will not respond to these comments, but adolescents who cannot accept comments from their environment tend to blame themselves. This study aims to determine the effect of body shaming on self-blaming in students of SMP Negeri 27 Banjarmasin. This study used an observational method with a cross-sectional design and random sampling and obtained 239 samples. The analysis technique uses simple linear regression. The instruments used in this study were the body shaming scale by Vargas and the self-blaming scale by Coleman. The independent variable in this study is body shaming, and the dependent variable is self-blame. The results showed that there was an effect of body shaming on self-blaming in students of SMP Negeri 27 Banjarmasin. This study concluded that body shaming by students of SMP Negeri 27 Banjarmasin was classified as very high and resulted in students who were victims of body shaming experiencing moderate self-blaming. There is a significant influence between body shaming and self-blaming on students.